Evaluasi Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM) sebagai Upaya Meningkatkan Perekonomian Masyarakat di Kelurahan Petemon Kecamatan Sawahan Kota Surabaya - Isnatul Huda; Achluddin Ibnu Rochim; Indah Murti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
In an effort to improve the community's economy in Petemon Village, Sawahan Subdistrict, Surabaya City, this research analyzes the empowerment of Micro, Small and Medium Enterprises (MSMEs). The results show that although programs to encourage MSMEs exist, their implementation is not optimal. One of the problems found is the lack of coordination between related agencies, the lack of training and capital distributed for MSMEs, and the lack of monitoring the growth of MSMEs. According to this study, although efforts have been made to support the applicable laws, the implementation of the program needs to be improved, especially in terms of fair distribution, effective socialization, and assistance that suits the needs of MSMEs.